An approximate assessment of the production levels of the Italian fishing fleet in the Mediterranean Sea during selected years in comparison with the analogous previous estimates - ROMANELLI, MICHELE (Mediterranean Marine Science, 2020)
During the past two decades, the organization Sea Around Us (based at the Fisheries Centre in British Columbia, Canada) has been carrying out the relevant task of reconstructing national statistics on marine fisheries for almost all countries and territories to fill information gaps and correct the general trend of severe underestimation of the “true” level of catches, discards and landings. A recent reconstruction of this kind showed that the annual catches by the Italian fleet fishing in the Mediterranean Sea had been presumably underestimated during most of the 1950-2010; in the 1970-1995 sub-period, they would have ranged from 0.7-1.1 million metric tons per year. However, comparisons with the landings for the few years for which there are “independent” estimates (i.e., not based on official statistics) show that many more bivalve molluscs and fewer “small pelagics” were caught and that the highest annual outputs reported by Sea Around Us should be presumably cut by 25%-35%.